2019
DOI: 10.1002/nau.23928
|View full text |Cite
|
Sign up to set email alerts
|

Cough associated detrusor overactivity in women with urinary incontinence

Abstract: Aims This is the first study that attempts to define different forms of cough associated detrusor overactivity (CADO). Current literature lacks clarity regarding the types of CADO and clinical epidemiology. Methods Retrospective review of all adult women who underwent urodynamics for urinary incontinence (UI) over 7 years. Patients were stratified into four types: I, leak with CADO; II, leak with cough; III, leak with both; IV, leak with neither. Cough spike immediately preceding detrusor overactivity was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…No standard treatment exists for CADO. Sinha et al 8 classified UDS results with CADO into four categories as incontinence associated with I: CADO (UUI), II: with cough (SUI), III: with both cough and CADO (mixed UI), and IV: with neither, and discussed the differences between them. For type II CADO associated with SUI, Koonings et al reported resolution of CADO after surgery for SUI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No standard treatment exists for CADO. Sinha et al 8 classified UDS results with CADO into four categories as incontinence associated with I: CADO (UUI), II: with cough (SUI), III: with both cough and CADO (mixed UI), and IV: with neither, and discussed the differences between them. For type II CADO associated with SUI, Koonings et al reported resolution of CADO after surgery for SUI.…”
Section: Discussionmentioning
confidence: 99%
“…For type II CADO associated with SUI, Koonings et al reported resolution of CADO after surgery for SUI. 7 For Type I cases, Sinha et al 8 stated that surgery for SUI is inappropriate and management with a refractory OAB regimen is logical, but there are no reports of actual treatment. Although our patient complained of incontinence during Pabd, UI due to type I CADO indicated UUI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quanto ao relato de rinite e sinusite, as mesmas apresentaram associação com os sintomas de bexiga hiperativa pelo ICIQ-OAB (p = 0,03). Isto pode ser ocasionado pela tosse ou espirros como resultado do aumento da pressão intra-abdominal e de uma contração do detrusor, o que leva a IU [32].…”
Section: Consideramos a Remodelação Do Tecido Conjuntivo Associado Ao...unclassified